Cultivo orgânico de macieiras em região subtropical úmida: da implantação ao quarto ciclo - Tico, Barbara Moura (2023)
A apple is one of the most widely produced and economically important fruits. However, its organic production is not yet significant, especially in Brazil, where cultivation climatic conditions are not the most suitable and impose challenges in overcoming dormancy as well as controlling key pests and diseases of the crop, which are usually managed with the use of pesticides. The present study aimed to analyze, as a case study, the organic management of this cultivar under the conditions in which the experiment was conducted, evaluate the post-harvest quality of stored fruits, and assess the efficiency of different concentrations of hydrogen peroxide and garlic spray in overcoming the dormancy of the Eva Rubi cultivar, which has productive potential in regions with mild winters. The work was conducted in research areas of the Rural Development Institute of Paraná and in the Horticulture laboratory of the Federal Technological University of Paraná, Pato Branco campus. The cultivation steps were described, from pre-implantation of seedlings to harvest, advising on fertilization, pruning, and presenting procedures for pest and disease control. Productivity, fruit quality, soil fertility progression in the organic system, plant fertility, phytosanitary management, as well as the efficiency of bud inducers (hydrogen peroxide and garlic spray, at concentrations of 0%, 5%, 10%, 15%, and 20%) were evaluated in the municipalities of Pato Branco, Palmas, and Lapa, in addition to the post-harvest quality of stored fruits. Improvements were observed in soil fertility in the organic system and the proper management of biological interference agents. However, it is still necessary to study efficient protocols to prevent economic damages caused by Marssonina coronaria. Storage at 1°C of the fruits was possible for 30 days without loss of quality. The dormancy overcoming methods showed no effect or toxicity to the plants, with garlic spray standing out as a potential use, but further testing is still necessary. The 'Eva Rubi' and 'Julieta' cultivars demonstrated aptitude for organic production in the southwestern region of Paraná.